Effects of Covid-19 on the psychological well-being of employees in South Africa - Ashruf, Ahmed (University of the Witwatersrand, Johannesburg, 2022)
On January 30, 2020, the World Health Organization (WHO) declared the Covid-19 virus to be a pandemic (Zanke et al., 2020, p.49). The virus first spread in South Africa when a traveller returned to the country after visiting Italy. To stop the infection from spreading South Africa implemented a national lockdown as per the Disaster Management Act, Regulations: Alert level 5 on the 26th of March 2020. South Africans were only permitted to leave their homes for medical crises, food, and medication (Villani et al., 2021, p.2). Furthermore, universities and schools were shut down whereby some functioned online, intern-regional, and international travel was suspended. During this time, all kinds of meetings were prohibited. Inter-regional travel became feasible six month later, and five months later it was conceivable for those living in various regions to be able to return to their homes (Villani et al., 2021, p.2). However, front line workers were only permitted at the time to attend work while other companies transitioned to remote work
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Management to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Effects of Covid-19; Employees; South Africa; UCTD; SDG-3: Good health and well-being